2017
DOI: 10.18332/tpc/76623
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of smoking cessation and abstinence in a Russian smoking-cessation center

Abstract: INTRODUCTION Smoking prevalence in Russia is one of the highest in the world. It leads to significant damage to the National Health Service. The purpose of the present research was to assess the effectiveness of a qualified smoking-cessation (SC) center in Moscow, and to identify the main determinants of smoking cessation. METHODS The subjects of this study were a cohort of smokers (n=524) who had attended the SC service in Moscow between 2012-2015. They were followed, for at least 6 months after receiving th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Perhaps one can claim that one of the important factors that can persuade people to stop hookah is to create strong motivation in them by the advice of their loved ones. A study found that those who are motivated to stop smoking are four times more likely to quit it than those with low motivation (Levshin & Slepchenko, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps one can claim that one of the important factors that can persuade people to stop hookah is to create strong motivation in them by the advice of their loved ones. A study found that those who are motivated to stop smoking are four times more likely to quit it than those with low motivation (Levshin & Slepchenko, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…TCCs can meet the needs of HSs and provide effective educational interventions to help them quit. By providing exclusive cessation services to hookah users, TCCs can be as effective in HS cessation as in cigarette smoking [58,59]. The existence of specialized smoking cessation clinics can point to the seriousness of this matter and encourage people to think about the adverse effects of HS.…”
Section: Discussionmentioning
confidence: 99%
“…Psychosocial characteristics, such as motivation [25,29,30] and a high level of confidence [31,32], may interfere with the result of smoking cessation attempts. The frequency of success was four times higher when the smokers' readiness to quit escalated from the "precontemplation" stage to the "contemplation" stage and two times higher from the "preparation" stage to the "action" stage [25].…”
Section: Discussionmentioning
confidence: 99%